GNRHR-related central hypogonadism with spontaneous recovery - case report - Darja Šmigoc Schweiger; Maja Davidović Povše; Katarina Trebušak Podkrajšek; Tadej Battelino; Magdalena Avbelj Stefanija (BMC, 2022)
Abstract Background Congenital hypogonadotropic hypogonadism (CHH) is a clinically and genetically heterogeneous disease characterized by absent or incomplete puberty and infertility. Clinical characteristics are secondary to insufficient gonadotropin secretion, caused by deficient gonadotropin-releasing hormone (GnRH) production, secretion, or action. Loss-of-function variants of the gonadotropin-releasing hormone receptor (GNRHR) are associated with CHH without anosmia. CHH was previously considered a permanent condition, but in the past two decades, cases of spontaneous recovery of CHH have been reported. The reversal of hypogonadism in CHH is currently unpredictable, and can happen unnoticed. Case presentation The male proband was diagnosed with CHH due to compound heterozygosity for two previously reported pathogenic missense variants in the GNRHR gene, NM_000406.2:c.416G > A (NP_000397.1:p.Arg139His) and c.785G > A (p.Arg262Gln) at 16 years of age. In addition to arrested partial puberty, he had a low testosterone level, gonadotropins in the range of early puberty, and a normal inhibin B level. A therapy with increasing doses of intramuscular testosterone undecanoate was received for 2.5 years, while there was no change in testicular volume. At the age of 19 years, testosterone supplementation was interrupted. During the next two years, he had spontaneous pubertal development to achieve a testicular volume of 20 mL, with normal adult levels of gonadotropins and testosterone. Conclusions Genetic diagnostics can help discriminate congenital hypogonadotropic hypogonadism, deserving therapeutic intervention, from the self-limited constitutional delay of growth and puberty (CDGP). Patients with GNRHR associated hypogonadism can experience spontaneous recovery of the hypothalamic-pituitary-gonadal axis. Spontaneous testis enlargement in patients with central hypogonadism not taking gonadotropins or pulsatile GnRH therapy can indicate recovery of hypogonadism.